Climate change and nutrition: Creating a climate for nutrition security - Tirado, Maria Cristina; Crahay, Philippe; Mahy, Lina; Zanev, Catherine; Neira, Maria; Msangi, Siwa; Brown, Rebecca; Scaramella, Carlo; Costa Coitinho, Denise; Müller, Alexander (SAGE Publications, 2013)
Climate change further exacerbates the enormous existing burden of undernutrition. It affects food and nutrition security and undermines current efforts to reduce hunger and promote nutrition. Undernutrition in turn undermines climate resilience and the coping strategies of vulnerable populations.The objectives of this paper are to identify and undertake a cross-sectoral analysis of the impacts of climate change on nutrition security and the existing mechanisms, strategies, and policies to address them.A cross-sectoral analysis of the impacts of climate change on nutrition security and the mechanisms and policies to address them was guided by an analytical framework focused on the three ‘underlying causes’ of undernutrition: 1) household food access, 2) maternal and child care and feeding practices, 3) environmental health and health access. The analytical framework includes the interactions of the three underlying causes of undernutrition with climate change, vulnerability, adaptation and mitigation.Within broad efforts on climate change mitigation and adaptation and climate-resilient development, a combination of nutrition-sensitive adaptation and mitigation measures, climate-resilient and nutrition-sensitive agricultural development, social protection, improved maternal and child care and health, nutrition-sensitive risk reduction and management, community development measures, nutrition-smart investments, increased policy coherence, and institutional and cross-sectoral collaboration are proposed as a means to address the impacts of climate change to food and nutrition security. This paper proposes policy directions to address nutrition in the climate change agenda and recommendations for consideration by the UN Framework Convention on Climate Change (UNFCCC).Nutrition and health stakeholders need to be engaged in key climate change adaptation and mitigation initiatives, including science-based assessment by the Intergovernmental Panel on Climate Change (IPCC), and policies and actions formulated by the UN Framework Convention on Climate Change (UNFCCC). Improved multi-sectoral coordination and political will is required to integrate nutrition-sensitive actions into climate-resilient sustainable development efforts in the UNFCCC work and in the post 2015 development agenda. Placing human rights at the center of strategies to mitigate and adapt to the impacts of climate change and international solidarity is essential to advance sustainable development and to create a climate for nutrition security.